MEDAN MAKNA VERBA MEMUKUL DALAM BAHASA DIALEK MELAYU SUKADANA - Duan, Elisabet Bota; Patriantoro, Patriantoro; Amir, Amrian (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe general problem in this study is how the meaning component of the meaning field verbs hit in BMDS. The general problem is then limited to two sub-problems namely, the component of meaning, and the semantic function. The purpose of this research is to describe the two constrained problems, while the benefits are this research can provide input for other language researchers who are interested in knowing BMDS, can provide knowledge of the Indonesian people, especially West Kalimantan about the meaning field verbs hit BMDS, this research can add insight and the experience of researchers in writing scientific papers relating to language, especially BMDS, this research can be used as a reference for future researchers who will study BMDS. This research can describe the variation of very valuable vocabulary wealth, especially Medan Meaning of Verba. This research uses descriptive method, in the form of qualitative. The source of the research data is the Sukadana Dialect Malay Language which was spoken by informants in Pulau Kumbang Village, Simpang Hilir District, North Kayong Regency. The data can be interviewed about the verb meaning field with the recorded informant then translated and recorded. Data collection techniques used in this study are recording techniques, Captivating Involvement Techniques (SLC), Technique of Seeing Non-Involvement and Note Techniques.Keywords: meaning field, verb, hit